2023
DOI: 10.1200/go.22.00366
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Breast Cancer Care Delivery at the National Cancer Institute of Sri Lanka: Does Language Play a Role?

Abstract: PURPOSE This study sought to examine whether there was an association between language barriers and patient satisfaction with breast cancer care in Sri Lanka. METHODS A telephone-based survey was conducted in the three official languages (Sinhala, Tamil, or English) among adult women (older than 18 years) who had been treated for breast cancer within 6-12 months of diagnosis at the National Cancer Institute of Sri Lanka. The European Organisation for Research and Treatment of Cancer Satisfaction with Cancer Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“… 18 A survey among Tamil and Sinhalese patients with breast cancer in Sri Lanka, a country with multiethnic (Sinhalese, Tamils, Moors, and Burghers) and multilinguistic societies with three different official languages (Sinhalese, Tamil, and English), is reported in this Special Edition. Thanabalasingam et al 19 showed that patients who speak the same language as their health care providers showed a higher level of satisfaction with the care received.…”
Section: Culturally Sensitive Cancer Care In Apmentioning
confidence: 99%
“… 18 A survey among Tamil and Sinhalese patients with breast cancer in Sri Lanka, a country with multiethnic (Sinhalese, Tamils, Moors, and Burghers) and multilinguistic societies with three different official languages (Sinhalese, Tamil, and English), is reported in this Special Edition. Thanabalasingam et al 19 showed that patients who speak the same language as their health care providers showed a higher level of satisfaction with the care received.…”
Section: Culturally Sensitive Cancer Care In Apmentioning
confidence: 99%